Local wisdom-friendly youth health services for students of Citra Bangsa Junior High School, Limo District, Depok - Ritanti Ritanti; Mareta Dea Rosaine; Yuri Nurdiantami (Community Empowerment, 2022)
Adolescent health services for junior high school (SMP) students are very important in the effort to create a drug-free young generation, because they are the nation's next generation who will determine the nation's future fate. The primary objective of this program is to improve students' knowledge, attitudes, and behavior about drugs and adolescent health; develop the character of healthy, drug-free teenagers; and develop junior high school students' creativity in peer education as a promotional effort to create drug-free schools. Health education, training, mentoring, monitoring, and evaluation are some of the methods used. The assessment revealed a 98.2% increase in knowledge, a 94.7% increase in attitude, and a 93% increase in behavior. At Citra Bangsa Junior High School, the youth health service program "BERSINAR" (Bersih Narkoba) has also proven to be effective as a peer companion program. The outcome of this program suggest that schools and health centers play an active role in ongoing coaching, mentoring, monitoring, and evaluation activities.